Impact of organic acids supplementation to hardwood spent sulfite liquor as substrate for the selection of polyhydroxyalkanoates-producing organisms - Queirós, Diogo (2021)
The effectiveness of polyhydroxyalkanoates (PHAs) production process from a waste stream is determined by the selection of a suitable mixed microbial culture (MMC). In this work, a feedstock from the paper industry, hardwood spent sulfite liquor (HSSL), supplemented with short-chain organic acids (SCOAs) to simulate a fermented effluent, was used as substrate to enrich a MMC in PHA-storing microorganisms. A stable culture was quickly established, and during the accumulation step the selected MMC reached a maximum PHA content of 34.6% (3HB:3HV-76:24). The bacterial community was analyzed through FISH analysis. Bacteria belonging to the four main classes were identified: Betaproteobacteria (44.7 ± 2.7%), Alphaproteobacteria (13.6 ± 1.3%) and Gammaproteobacteria (2.40 ± 1.1%) and Bacteroidetes (9.20 ± 3.8%). Inside the Betaproteobacteria class, Acidovorax (71%) was the dominant genus.